Keefektifan Teknik Structured Learning Approach untuk Meningkatkan Disiplin Belajar Siswa SMA Negeri 2 Sumenep - Nur Hidayah; Anis Tri Yuliana (STKIP PGRI SUMENEP, 2020)
This study aims to test the effectiveness of the structured learning approach to improve learning discipline. The design used in this study is one group pretest-posttest design. The subjects of the study were 8 students of class XI IPA who had low discipline learning scores. Measurement of student learning discipline is done repeatedly before and after treatment is given to see the consistency of the research subject conditions. Testing or measurement of effectiveness is carried out using The Wilcoxon Signed-rank test then proceed to the next test that is paired t-test. The findings of this study prove that the structured learning approach is effective in improving the discipline of student learning at Sumenep 2 Public High Schools.